Intragraft gene expression in native kidney BK virus nephropathy versus T cell–mediated rejection: Prospects for molecular diagnosis and risk prediction. Issue 12 (29th May 2020) - Adam, Benjamin A.; Kikic, Zeljko; Wagner, Siegfried; Bouatou, Yassine; Gueguen, Juliette; Drieux, Fanny; Reid, Graeme; Du, Katie; Bräsen, Jan H.; D'Agati, Vivette D.; Drachenberg, Cinthia B.; Farkash, Evan A.; et al.
Abstract : Novel tools are needed to improve diagnostic accuracy and risk prediction in BK virus nephropathy (BKVN). We assessed the utility of intragraft gene expression testing for these purposes. Eight hundred genes were measured in 110 archival samples, including a discovery cohort of native kidney BKVN (n = 5) vs pure T cell–mediated rejection (TCMR; n = 10). Five polyomavirus genes and seven immune‐related genes (five associated with BKVN and two associated with TCMR) were significantly differentially expressed between these entities (FDR < 0.05). These three sets of genes were further evaluated in samples representing a spectrum of BK infection (n = 25), followed by a multicenter validation cohort of allograft BKVN (n = 60) vs TCMR (n = 10). Polyomavirus 5‐gene set expression reliably distinguished BKVN from TCMR (validation cohort AUC = 0.992), but the immune gene sets demonstrated suboptimal diagnostic performance (AUC ≤ 0.720). Within the validation cohort, no significant differences in index biopsy gene expression were identified between BKVN patients demonstrating resolution (n = 35), persistent infection (n = 14) or de novo rejection (n = 11) 6 months following a standardized reduction in immunosuppression. These results suggest that, while intragraft polyomavirus gene expression may be useful as an ancillary diagnostic for BKVN, assessment for concurrent TCMR and prediction of clinical outcome may not be feasible with current molecular tools. Abstract : A comparison of the molecular phenotype of native kidney biopsies with BK virus nephropathy versus transplant kidney biopsies with T cell–mediated rejection demonstrates significant differences in polyomavirus gene expression, but not immune‐related gene expression, between these two entities.